Disseminated tuberculosis caused by Mycobacterium bovis presenting as a tongue base mass. (14th October 2018) - Pratt, Sarah; Henderson, Arthur; Gillett, Stuart
Abstract : An 80-year-old woman presented with dysphagia, odynophagia and progressive weight loss. Initial investigations suggested a large base of tongue squamous cell carcinoma. At panendoscopy, biopsies were taken which revealed granulomatous inflammation with multinucleated giant cells and areas of caseous necrosis. Acid-fast bacilli were identified on Ziehl-Neelsen stain and the appearances were consistent with Mycobacterium bovis . Closer inspection of the patient's medical history revealed that she had previously undergone right hemicolectomy for an ascending colon stricture. The histology had shown granulomatous inflammation consistent with intestinal tuberculosis but no systemic treatment had been instigated at the time. This case highlights the importance of taking a detailed clinical history as well as the need to be cognisant of tuberculosis masquerading as cancer in the head and neck.